1986
DOI: 10.1152/ajpheart.1986.251.2.h405
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and chronotropic sensitivity to beta-adrenergic stimulation in sepsis

Abstract: An organism's cardiovascular response to sepsis is at least partly dependent on hormonal and neural modulation of myocardial function. We have investigated both intrinsic myocardial performance and one aspect of myocardial sensitivity to beta-adrenergic stimulation in a model of sepsis in which animals, at the time studied, exhibited bacteremia, normal arterial blood pressure and cardiac output, elevated heart rate, and elevated plasma catecholamines. Intrinsic myocardial contractile function, studied with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…The observation that responsiveness of isolated atria to isoproterenol is identical in mice before and 4 h post-LPS, corroborates previous reports which were unable to show impaired chronotropic responsiveness to adrenergic stimulation in experimental sepsis (Smith et al, 1986;Barker et al, 1990). McDonough and colleagues have shown that in early sepsis, despite intrinsic myocardial contractile dysfunction, the ability of the heart to modulate its inotropic and chronotropic state in response to β-adrenergic stimulation is intact or even increased (Smith et al, 1986;Smith and McDonough, 1998;Barker et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observation that responsiveness of isolated atria to isoproterenol is identical in mice before and 4 h post-LPS, corroborates previous reports which were unable to show impaired chronotropic responsiveness to adrenergic stimulation in experimental sepsis (Smith et al, 1986;Barker et al, 1990). McDonough and colleagues have shown that in early sepsis, despite intrinsic myocardial contractile dysfunction, the ability of the heart to modulate its inotropic and chronotropic state in response to β-adrenergic stimulation is intact or even increased (Smith et al, 1986;Smith and McDonough, 1998;Barker et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…These data demonstrate that decreased endorgan responsiveness to the adrenergic system does not play a role in the alteration of HRV parameters following sepsis. The involvement of the myocardium in the injury resulting from sepsis has been somewhat controversial (Smith et al, 1986;Smith and McDonough, 1998;Barker et al, 1990;Matsuda et al, 2000). The observation that responsiveness of isolated atria to isoproterenol is identical in mice before and 4 h post-LPS, corroborates previous reports which were unable to show impaired chronotropic responsiveness to adrenergic stimulation in experimental sepsis (Smith et al, 1986;Barker et al, 1990).…”
Section: Discussionsupporting
confidence: 62%
“…The rate of contraction of isolated atrial preparations from endotoxemic hearts also was significantly increased in the early-stage endotoxemia and remained increased until late-stage endotoxemia. These results are similar to those reported by others [29, 46, 47]. The rate of contractions in both stages was not affected by Oro-A or AVP, suggesting that both agents at the concentrations used do not directly affect these tissues or exhibit nonspecific effects.…”
Section: Discussionsupporting
confidence: 92%
“…So far, this phenomenon has only been described in the heart or atria isolated from rats in the early phase of sepsis induced by cecal ligation and puncture (8,9). Our results agree with the data obtained by Barker et al (8), who showed that the positive chronotropic effect of ISO and FEN was more markedly potentiated than that of PRE; this difference was attributed to the activation of " 2 -adrenoceptors by ISO and FEN and to the preferential activation of " 1 -adrenoceptors by PRE (8).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compared to tissues from control animals, the tachycardia elicited by the "-adrenoceptor agonists ISO, prenalterol (PRE), and fenoterol (FEN) was enhanced in isolated right atria obtained from rats subjected to cecal ligation and puncture, suggesting that the active population of "-adrenoceptors changes during septic shock (8,9). The evidence is, however, not unequivocal.…”
Section: Introductionmentioning
confidence: 99%